Temperature dependent dielectric properties of Au/ZnO/n-Si heterojuntion. (14th March 2018) - Kocyigit, Adem; Orak, İkram and Turut, Abdulmecit
Abstract: Owing to importance of ZnO in electronics, Au/ZnO/ n -type Si device was fabricated to investigate its dielectric properties by aid of capacitance-conductance-voltage measurements. While the ZnO thin film layer on the n -type Si was formed by atomic layer deposition (ALD) technique, the rectifying and ohmic contacts were obtained by thermal evaporation. The surface morphology of ZnO thin film was characterized using atomic force microscopy (AFM) to show its compatibility as interfacial layer in the Au/ZnO/ n -type Si device. The dielectric properties of the device were examined in terms of dielectric parameters such as dielectric constant ( ε ′), dielectric loss ( ε ″), loss tangent (tan δ ), the real and imaginary parts of electric modulus ( M ′ and M ″ ) and ac electrical conductivity ( σ ) depending on applied voltages (from −1 to 2 V) and temperatures (from 140 K to 360 K) ranges. The results have revealed that interfacial polarization and charge carriers are the important parameters to affect the dielectric properties of the device with changing temperature. The device can be used at wide range temperatures for diode applications.